2019
DOI: 10.1371/journal.pone.0208701
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prognostic factors, survival, and recurrence incidence of triple negative breast cancer patients, a single center study in Iran

Abstract: BackgroundBreast cancer is the second leading cause of death due to cancer in women. Triple negative breast cancer (TNBC) is a subgroup with unique behavior. There is a controversy in organ involvement in metastasis. In this study, we planned to define the prognostic factors, survival, and recurrence incidence of patients.Materials and methodAmong the 583 patients with breast mass referred to hematology and oncology clinic in Shariati hospital, Tehran, Iran from March 2005 to March 2015, fifty four patients en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The 5-year OS rate in our study was 88% which is comparable to that reported by a study from China where the 5-year OS rate was 88.5% 17 , and another study from Iran where the 5-year survival was 86.1% 18 . On the other hand, the 5-year OS rates were much lower in other studies.…”
Section: Discussionsupporting
confidence: 87%
“…The 5-year OS rate in our study was 88% which is comparable to that reported by a study from China where the 5-year OS rate was 88.5% 17 , and another study from Iran where the 5-year survival was 86.1% 18 . On the other hand, the 5-year OS rates were much lower in other studies.…”
Section: Discussionsupporting
confidence: 87%
“…The plausibility of diagnostic MMG to inform such crucial clinical details is encouraging, having the potential to fast-track treatment decision making in clinical practice. This is particularly prudent for TNBC, and the inherent threat and aggressive natural history of TNBC is irrefutable in surgical and medicooncological literature [65]. MMG remains the standard diagnostic tool in worldwide breast cancer screening programmes, with screening mammography performed 38 million times per annum in the United States according to the Mammography Quality Standards Act and Program [66], as well as diagnostic sensitivity and specificity rates in excess of 85% [67].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 583 patients, Mousavi et al 24 demonstrated that lymph node involvement was the only prognostic factor related to decreased DFS in TNBC. However, other studies have demonstrated that a larger tumor size and residual tumor burden correlate with a higher recurrence risk and lower DFS in TNBC 25 .…”
Section: Discussionmentioning
confidence: 99%